Serafina and the splintered heart - Beatty, Robert, 1963- (Disney-Hyperion, 2017)
When a mysterious threat moves towards Biltmore, bringing with it violent storms and flooding, Serafina must fight to defend all she loves and become everything that she is meant to be.